VISCERAL ABDOMINAL PAIN AND OPPORTUNITIES OF SPASMOLYTIC TREATMENT - E.A. Kornienko; E.L. Igumenova ("Paediatrician" Publishers LLC, 2008)
Results of treatment of 30 children with visceral abdominal pain caused by different etiological factors with neurotropic selective m9cholinergic antagonist hyoscine butilbromide (buscopan) are presented in this article. Two groups of children were treated with hyoscine butilbromide and drotaverine accordingly. Administration of hyoscine butilbromide allows to stop pain in 93% of patients; mean duration of abdominal pain was 3,4 ± 1,2 days (4,2 ± 1,4 days in children treated with drotaverine, р < 0,05). Activity of dyspeptic disorders was decreased at the time of treatment. a tolerance to hyoscine butilbromide was satisfactory, and no adverse events were registered. hyoscine butilbromide is effective in treatment of visceral abdominal pain in children, allowing shortening its duration more actively then drotaverine. Key words: children, visceral abdominal pain, hyoscine butilbromide.